Role of combination of l‐arginine and α‐tocopherol in renal transplantation ischaemia/reperfusion injury: a randomized controlled experimental study in a rat model - Shokeir, Ahmed A.; Barakat, Nashwa; Hussein, Abdel‐Aziz M.; Awadalla, Amira; Abdel‐Aziz, Azza; Abo‐Elenin, Hassan (BJU international, 2011)
What’s known on the subject? and What does the study add? Renal ischaemia/reperfusion (I/R) injury is an inevitable consequence of kidney transplantation. It contributes to delayed graft function (DGF), acute renal failure and graft rejection. The present study investigates for the first time the impact of a combination of l‐arginine and alpha tocopherol on the renal ischemia/reperfusion injury in a rodent model of kidney transplation. We found that concomitant administration of l‐arginine and α‐tocopherol has a more protective effect and synergistic antioxidant effect on ischaemia/reperfusion injury in transplanted rat kidneys. OBJECTIVES To investigate the role of l‐arginine and α‐tocopherol in ischaemia/reperfusion injury in a kidney transplanted rat model. MATERIALS AND METHODS In total, 40 male Sprague‐Dawley rats subjected to renal transplantation received FK506 (tacrolimus) to overcome early acute rejection episodes. Animals were divided randomly into four groups (ten rats each). Group I were treated with FK506 (2 mg/kg/bw/day) and served as the control group. Group II were treated with l‐arginine 300 mg/kg/bw. Group III were treated with α‐tocopherol 30 mg/kg/bw. Group IV were treated with l‐arginine and α‐tocopherol. Urine and blood samples were taken at 0 (before operation), 2, 7 and 14 days post‐transplantation for estimation of urine sodium, creatinine, fractional excretion of sodium, serum creatinine, sodium and blood urea nitrogen. Histological examination and measurement of malondialdehyde in kidney tissues were also performed. RESULTS Serum creatinine and blood urea nitrogen significantly decreased in l‐arginine and α‐tocopherol, as well as combination groups, compared to the control group. Malondialdehyde was significantly decreased in the combination group compared to l‐arginine and α‐tocopherol alone. Histological examination of the control group showed that acute tubular necrosis was markedly decreased in transplanted kidneys treated with a combination of both l‐arginine and α‐tocopherol. CONCLUSIONS Concomitant administration of l‐arginine and α‐tocopherol has a more protective effect and synergistic antioxidant effect on ischaemia/reperfusion injury in transplanted rat kidneys.